Method for preparing mesophase pitch from polycarbonate modified impregnated pitch
By mixing polycarbonate with impregnated bitumen and carbonizing it with heating and heating, the problems of poor fluidity and high softening points of the mesophase bitumen are solved, and mesophase bitumen with high content, low softening points and good fluidity are prepared.
Patent Information
- Application Number
- CN202510220934.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-27
- Publication Date
- 2025-05-02
AI Technical Summary
The existing mesophase asphalt made of modified impregnated asphalt with polymer additives has problems of poor fluidity and high softening points.
Mesophase asphalt is prepared by mixing polycarbonate with impregnated bitumen and heating and carbonizing under nitrogen protection. The molecular weight of polycarbonate is 500-6000, and the weight ratio is 1: (5-20) of impregnated asphalt.
The obtained mesophase asphalt content is 100%, the softening point is reduced to 230°C, and it has high fluidity and suitable structural characteristics, making it suitable for the preparation of high-performance carbon materials.
Smart Images

Figure CN119912958A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the preparation of carbon materials, and in particular to a method for preparing mesophase asphalt by using polycarbonate modified impregnated asphalt. Background Art
[0002] Pitch-based carbon fibers can be divided into isotropic general-purpose pitch-based carbon fibers and anisotropic mesophase pitch-based carbon fibers. Isotropic pitch-based carbon fibers have low mechanical properties and thermal conductivity and are mostly used as thermal insulation materials or activated carbon fibers. The optical texture of mesophase pitch is anisotropic, and it has high carbon content, regular molecular arrangement, high orientation, and good fluidity. It is an excellent precursor for preparing needle coke, carbon foam, high-performance pitch-based carbon fibers, etc. Pitch-based carbon fibers prepared with mesophase pitch as raw material have the characteristics of light weight, high strength, high modulus, and high thermal conductivity. They are widely used in military defense, aerospace, wind power generation, automotive engineering, sports equipment and other fields. However, the high price limits the wide application of pitch-based carbon fibers in many industries. It is particularly important to find a low-cost raw material to reduce the preparation cost of pitch-based carbon fibers. Coal tar pitch is widely used in carbon materials due to its large output and high carbon content. The high reactivity and aromaticity of coal tar pitch result in poor fluidity of the prepared mesophase pitch during spinning, and the prepared asphalt-based carbon fibers have poor performance and are not suitable for the preparation of high-performance carbon materials. Therefore, it is necessary to modify the coal tar.
[0003] Mesophase asphalt can be prepared by hydrogenating coal tar pitch. Hydrogenation can be achieved by adding hydrogen or adding a hydrogen donor. Its mechanism is to introduce cycloalkane structure into the precursor asphalt and retain it during the formation of the mesophase, thereby improving the fluidity of the mesophase asphalt. Hydrogenation is an effective method for preparing high-quality mesophase asphalt. However, the by-products formed during the carbonization process are difficult to remove, and the method is costly and expensive, which limits industrial production. The alkylation modification method accelerates the dealkylation rate during the mesophase conversion process and increases the content of the mesophase structure. The disadvantages of this method are almost the same as those of the hydrogenation modification method. As a commonly used method for preparing mesophase asphalt, the co-carbonization method uses polymers as additives, which not only promotes the formation of the mesophase and increases the content of the mesophase, but also has the advantages of simple operation and low cost. There are three types of additives, namely rubber (such as styrene-butadiene rubber), plastics (such as styrene), and resins (such as epoxy resins).
[0004] By adding waste polystyrene to coal tar pitch to prepare mesophase pitch, the soluble mesophase increased from about 9% to 52%, the mesophase structure increased from 74% of the rough mosaic structure to 100%, and the methylene content increased significantly. The presence of more alkyl groups changed the characteristics of the mesophase molecules and improved the assembly of the mesophase molecules. Waste styrene-butadiene-rubber (WSBR) was added to petroleum asphalt to prepare petroleum-based mesophase pitch. Using WSBR as a modifier can significantly promote the formation of the mesophase. When the temperature is constant, the addition of WSBR makes the optical anisotropic crystal structure of the sample stronger and has better thermal stability. When the WSBR content is unchanged, the anisotropic structure content of the mesophase pitch increases with the increase of temperature. Naphthalene pitch is co-carbonized with polystyrene. The addition of polystyrene introduces more aliphatic side chains and cycloalkane structures, which are retained during the formation of the mesophase. By co-carbonizing polyvinylidene fluoride with catalytic cracking oil slurry, during the co-carbonization process of catalytic cracking oil slurry and polyvinylidene fluoride, polyvinylidene fluoride is thermally decomposed, and fluorine free radicals decompose to produce intermediates, and then these intermediates act as intermediate phase seeds to produce a large domain intermediate phase asphalt.
[0005] Polymers containing benzene rings and alkyl groups and coal tar pitch will pyrolyze and react with asphalt molecules during the preparation of mesophase asphalt. The generated aliphatic side chains will promote the formation of streamlined optical texture and improve fluidity of the mesophase asphalt. However, the mesophase asphalt obtained by modifying coal tar pitch with the above-mentioned polymer additives has problems such as poor fluidity, high softening point, high reaction temperature and long reaction time. Summary of the invention
[0006] In view of the problems of poor fluidity and high softening point of the existing mesophase asphalt prepared by using polymer additives to modify the impregnated asphalt, the present invention provides a method for preparing the mesophase asphalt by using polycarbonate modified impregnated asphalt, comprising the following steps: 1. Mixing polycarbonate and impregnated asphalt; 2. The mixture is heated and carbonized.
[0007] The softening point of the impregnated asphalt of the present invention is 80-130°C. Polycarbonate (PC) contains a large number of benzene rings and methyl structures. It is added as a modifier to the impregnated asphalt with low ash content and good fluidity for co-carbonization, and a mesophase asphalt with a mesophase content of 100% and a softening point of 230°C can be obtained. In the method of the present invention, the molecular weight of the polycarbonate is 500-6000. The weight ratio of the polycarbonate to the impregnated asphalt is 1:(5-20).
[0008] Furthermore, the toluene insoluble matter (TI) of the impregnated asphalt of the present invention is ≥7%, the quinoline insoluble matter (QI) is ≤0.7%, the coking value is ≥45%, the ash content is ≤0.1%, and the volatile matter is ≤60%.
[0009] In the method of the present invention, the carbonization atmosphere is nitrogen, the carbonization heating rate is 2-6°C / min, the carbonization temperature is 340-400°C, and the carbonization time is 5-10h.
[0010] Furthermore, the polycarbonate and impregnated asphalt mixture were purged with nitrogen for 10-20 min before carbonization.
[0011] The present invention aims at the problem that the performance of mesophase asphalt prepared by thermal polymerization of impregnated asphalt is poor. Polycarbonate is added to the impregnated asphalt to prepare the generation of mesophase asphalt, and the mesophase asphalt containing more aliphatic methylene structures is obtained, and the mesophase structure with high stacking degree and watershed type is obtained, and the structure of the asphalt molecules is suitable for TI and QI content and softening point. The small molecules generated after the thermal decomposition of polycarbonate can regulate the structure of the asphalt molecules, and the small molecules will react with the asphalt molecules to generate a large number of aliphatic methylene structures, which will promote the stacking of planar molecules, and will hinder the increase of the molecular weight of the planar molecules, reduce the increase of TI and QI content, increase the fluidity of the mesophase molecules, and reduce the softening point. These behaviors are conducive to the generation of the mesophase structure, which helps the macromolecular condensed aromatic hydrocarbon structures to stack with each other and helps to form a good mesophase morphology. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 Polarized micrographs of the impregnated asphalt (a) and the mesophase asphalt of Examples 1 to 4 (b to e).
[0013] Figure 2 Infrared spectra of the impregnated asphalt (PC-0%) and the mesophase asphalt obtained in Examples 1 to 4.
[0014] Figure 3 Thermogravimetric analysis diagrams of the impregnated asphalt and the mesophase asphalt obtained in Examples 1 to 4.
[0015] Figure 4 The Raman images of the impregnated asphalt and the mesophase asphalt obtained in Examples 1 to 4.
[0016] Figure 5 X-ray images of the impregnated asphalt and the mesophase asphalt obtained in Examples 1 to 4.
[0017] Figure 6 Schematic diagram of the mechanism of polycarbonate-modified impregnated asphalt of the present invention. DETAILED DESCRIPTION
[0018] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0019] The impregnated asphalt of the present invention is selected from Jining Chenxing Carbon Co., Ltd., with a softening point of 85°C, a toluene insoluble matter (TI) of 9%, a quinoline insoluble matter (QI) of 0.5%, a coking value of 45%, an ash content of 0.05%, and a volatile matter of 70%; the polycarbonate is selected from polycarbonate-110 of Chi Mei Industrial Co., Ltd. in Taiwan Province, China. Example 1
[0020] A method for preparing mesophase asphalt comprises the following steps: 1. Mix polycarbonate and impregnating asphalt evenly, wherein the amount of polycarbonate is 5% of the weight of the impregnating asphalt; 2. Purge the mixture of polycarbonate and impregnating asphalt with nitrogen for 10 minutes, and under nitrogen protection, heat it to 360°C at a heating rate of 2°C / min for carbonization, and the carbonization insulation time is 10 hours to obtain the intermediate phase asphalt after polycarbonate modified impregnating asphalt, marked as PC-5%. Example 2
[0021] A method for preparing mesophase asphalt comprises the following steps: 1. Mix polycarbonate and impregnating asphalt evenly, wherein the amount of polycarbonate is 10% of the weight of the impregnating asphalt; 2. Purge the mixture of polycarbonate and impregnating asphalt with nitrogen for 15 minutes, and under nitrogen protection, heat it to 380°C at a heating rate of 3°C / min for carbonization, and the carbonization insulation time is 8 hours to obtain the intermediate phase asphalt after polycarbonate modified impregnating asphalt, which is marked as PC-10%. Example 3
[0022] A method for preparing mesophase asphalt comprises the following steps: 1. Mix polycarbonate and impregnating asphalt evenly, wherein the amount of polycarbonate is 15% of the weight of the impregnating asphalt; 2. Purge the mixture of polycarbonate and impregnating asphalt with nitrogen for 20 minutes, and under nitrogen protection, heat it to 400°C at a heating rate of 4°C / min for carbonization, and the carbonization insulation time is 5 hours to obtain the intermediate phase asphalt after polycarbonate modified impregnating asphalt, which is marked as PC-15%. Example 4
[0023] A method for preparing mesophase asphalt comprises the following steps: 1. Mix polycarbonate and impregnating asphalt evenly, wherein the amount of polycarbonate is 20% of the weight of the impregnating asphalt; 2. Purge the mixture of polycarbonate and impregnating asphalt with nitrogen for 15 minutes, and under nitrogen protection, heat it to 340°C at a heating rate of 6°C / min for carbonization, and the carbonization insulation time is 10 hours to obtain the intermediate phase asphalt after polycarbonate modified impregnating asphalt, marked as PC-20%.
[0024] The morphology and microstructure of the pyrolysis products were observed using a reflective polarizing microscope (BM2100POL) from Jiangnan Yongxin Optics Co., Ltd. The sample to be tested was first heated and melted, and the product was poured into the mold while it was still hot when it was in the liquid phase. Then, epoxy resin and curing agent were injected to fix it. After standing for a period of time until the glue solidified, it could be polished and observed under a polarizing microscope. Figure 1 The polarized micrographs of the impregnated asphalt (a) and the mesophase asphalt obtained in Examples 1 to 4 (b to e), wherein the colored area is the mesophase structure. When the addition amount of polycarbonate is 0%, the morphology of the mesophase is a mosaic structure and the content is relatively low. When the addition amount of polycarbonate is 5%, the content of the mesophase increases, and the morphology changes from a mosaic structure to a streamline structure. When the addition amount of polycarbonate is 10%, the content of the mesophase reaches 100%, the streamline area becomes larger, and becomes a wide-area streamline structure; when the addition amount of polycarbonate continues to increase to 20%, the morphology of the mesophase changes from a streamline structure to a mosaic structure. The molecules of polycarbonate pyrolysis have a regulating effect on the asphalt molecules. After the addition of an appropriate amount of polycarbonate, the nucleation, development and fusion of the mesophase spheres are greatly promoted. During the thermal polymerization process, polycarbonate is decomposed into active molecules by heat. These active molecules undergo cross-linking reactions with the asphalt molecules, which is conducive to the stacking of large planar molecules and promotes the formation of the mesophase structure. The addition of an appropriate amount of polycarbonate is conducive to the formation of the mesophase structure. As the amount of polycarbonate added increases, the streamline structure will change into a mosaic structure. This is because after too much polycarbonate is added, more active molecules are produced, which leads to higher system pressure and more intense thermal shrinkage reactions, which to a certain extent hinder the spatial arrangement of the macromolecular structure, thus forming a mosaic structure.
[0025] Figure 2 The infrared spectra of the impregnated asphalt (PC-0%) and the mesophase asphalt obtained in Examples 1 to 4 are shown in Figure 3035. -1 The stretching vibration absorption peaks at 2908 cm-1 are attributed to the aromatic CH bond. -1 ~2842cm -1 The stretching vibration absorption peaks at 1588 cm-1 are attributed to the aliphatic CH bond. -1 The stretching vibration absorption peaks at 1435 cm-1 are attributed to the C=C double bond of the aromatic skeleton. -1 The bending vibration absorption peak of aliphatic methylene (including methylene in cycloalkane structure and aliphatic side chain) is 880cm -1 ~750cm -1 The peaks at 880cm- -1 The peak at 750 cm-1 belongs to the out-of-plane bending vibration of the isolated aromatic CH. -1 The out-of-plane bending vibration peaks of four adjacent aromatic CHs are shown in Figure 2. With the addition of PC, the Iar The value increases first and then decreases. When the amount of PC added is small, the small molecules decomposed by PC will help the asphalt molecules to polymerize into large aromatic molecules, and the aromaticity will increase accordingly. As the amount of PC added increases, the methylene structures become more, and this structure will regulate the asphalt molecules, and the aromaticity will decrease. The degree of in situ polycondensation of the mesophase asphalt shows a trend of first increasing and then decreasing. When a small amount of PC is added, PC decomposes small molecules under heat, and these small molecules undergo cross-linking reactions with asphalt molecules to generate methylene structures, which promote the stacking of molecules. With the addition of PC, the number of small molecules decomposed by PC increases sharply, causing the system pressure to increase, the methylene structure to decrease, and the stacked molecules to decompose. At 2908cm -1 ~2843cm -1 With 1435cm -1 The position is the stretching vibration peak of fat CH. With the increase of PC addition, the content of fat branched chains increases, while too much PC addition will lead to a decrease in the content of fat branched chains. The right amount of fat branched chains is conducive to the good fluidity of the mesophase asphalt. Too high aromaticity will lead to an increase in the softening point.
[0026] Figure 3 The thermogravimetric analysis diagram of the impregnated asphalt and the mesophase asphalt obtained in Examples 1 to 4 shows that with the addition of PC, the thermal stability of the mesophase asphalt deteriorates, indicating that the added PC has a regulating effect on the molecular structure of the asphalt. The thermal stability of PC-5% is the worst. After PC is added, during the thermal polymerization process, the small molecules decomposed by PC under heat will react with the asphalt molecules to form large molecular polycyclic aromatic hydrocarbons. Due to the low content of PC, the number of polycyclic aromatic hydrocarbons with stable structures generated is small, and some small molecules are in a discrete state, resulting in the worst thermal stability of PC-5%. The thermal stability of PC-20% is worse than that of PC-10% and PC-15% in the first and second stages. The reason is that the addition of too much PC will lead to the generation of a large number of small molecules, which will be stored in the mesophase asphalt. At the same time, these small molecules will increase the system pressure during the thermal polymerization process, causing some polycyclic aromatic hydrocarbons to decompose, resulting in poor thermal stability.
[0027] Figure 4 The Raman spectra of the impregnated asphalt and the mesophase asphalt obtained in Examples 1 to 4 show two types of characteristic peaks in the Raman spectrum of the mesophase asphalt, at 1350 cm -1 and 1580cm -1 The peaks near the D peak correspond to the D peak and the G peak. Generally, in pitch-based carbon materials, the D peak represents the disorder of organic matter and the defects between structural units. The greater the D peak intensity, the more defects the corresponding carbon material has. The G peak intensity reflects the aromatic structure of the sample and the stretching vibration of the atomic bonds in the SP2 hybridization plane of other carbon atoms. The area ratio of the D peak to the G peak (I D / I G ) is often used as a measure of the order of thermal polycondensation products, that is, I D / I G The smaller the value, the higher the order of the product molecular microstructure. D / I G The values are shown in Table 1. As the amount of PC added increases, I D / I G The value shows a trend of increasing first and then decreasing, and the order first decreases and then increases. When the PC content is small, PC decomposes under heat and cross-links with asphalt molecules to generate a large number of short fatty chains. As the amount of PC added increases, the content of short fatty chains continues to increase until it reaches a maximum when the PC content is 10%. At this time, the order of the mesophase asphalt is the worst. When a large amount of PC is added, I D / I G The value becomes smaller, and the order of the intermediate phase asphalt becomes better. With the addition of PC, a large number of small molecules are produced after PC pyrolysis, and the system pressure increases, resulting in a decrease in the fatty methylene structure and improved molecular flatness.
[0028] Table 1. I of mesophase asphalt at different PC addition amounts D / I G value
[0029] Figure 5 Table 2 is the X-ray image of the impregnated asphalt and the mesophase asphalt obtained in Examples 1 to 4, and Table 3 is the microscopic size statistics of the impregnated asphalt and the mesophase asphalt obtained in Examples 1 to 4. The influence of the amount of PC doping on the formation process of the mesophase asphalt molecules was further studied by analyzing the XRD spectra and microcrystalline parameters. The test sample showed a graphite (002) diffraction peak near 26°, which can qualitatively reflect the structural characteristics of the product molecules. The intermolecular spacing of the mesophase asphalt first decreased and then increased with the addition of PC. With the addition of PC, the aliphatic methylene structure in the mesophase asphalt increased. When the PC addition was 10%, the methylene structure was the most. At this time, the molecular interlayer spacing of the mesophase asphalt molecules was the smallest and the stacking height was the largest. This shows that aliphatic short hydrocarbons promote the stacking of large planar molecules, thereby reducing the molecular interlayer spacing and increasing the stacking height. As the amount of PC added increases, the pressure in the system increases, the aliphatic methylene knot decomposes, the stacking height of the mesophase asphalt molecular layer decreases, and the molecular interlayer spacing increases.
[0030] Table 2. Microscopic size of mesophase asphalt at different PC addition amounts
[0031] Table 3 is the component analysis of the impregnated asphalt and the mesophase asphalt obtained in Examples 1 to 4. With the increase of the amount of PC added, the QI content in the mesophase asphalt decreases, indicating that PC has the function of regulating the mesophase molecules. A large amount of PC is decomposed into small molecules by heat, which reduces the shrinkage of the mesophase asphalt and reduces the QI content. The addition of PC increases the H / C ratio, and the reduction when the PC content is 10% may be due to the large amount of fat methylene structures generated, which causes the H element to be removed in large quantities, thus causing the H / C to decrease. With the increase of the amount of PC added, the system pressure increases, the fat methylene structure decreases, and the H element returns to the mesophase asphalt molecule, and the H / C ratio gradually increases. The content of TI shows a trend of decreasing first and then increasing with the addition of PC, which also shows that the addition of PC can regulate the asphalt molecules. When the PC content is 5% and 10%, there are more fat methylene structures, which are conducive to the stacking of planar molecules and hinder the molecular weight of planar molecules from continuing to increase, so the TI content decreases. After too much PC is added, the fat methylene structure decreases, and the molecular weight of the planar molecules continues to increase, resulting in an increase in the TI content. As the amount of PC added increases, the softening point of the mesophase asphalt decreases first and then increases. This shows that the addition of an appropriate amount of PC will lower the softening point of the mesophase asphalt. The small molecules decomposed by heat from PC will have a regulatory effect on the asphalt molecules. When the PC content is 10%, there are more fatty methylene structures, the fluidity of the mesophase asphalt is better, and the softening point is lower. As the amount of PC added increases, the content of fatty methylene structures decreases, and the molecular weight of planar macromolecules continues to increase, resulting in stronger intermolecular forces and an increase in the softening point.
[0032] Table 3. Component analysis of mesophase asphalt at different PC addition amounts
[0033] The mechanism of preparing mesophase asphalt by using polycarbonate modified impregnated asphalt in the present invention is as follows: Figure 6 As shown in the figure, the impregnated asphalt presents a planar polycyclic aromatic molecular structure with fewer branches. When PC is thermally decomposed, it will generate aromatic molecules with benzene ring structures and branched structures. Such aromatic molecules will undergo dehydrogenation polymerization reaction with asphalt molecules, making the planar molecules larger, the molecular weight increased, and the aromaticity increased. At the same time, many branched structures will be added to the surface of polycyclic aromatic molecules, resulting in a decrease in flatness. The infrared test results show that the added branched structures are methylene structures. When there are more methylene structures, the XRD test results show that the molecular layer spacing between planar molecules is smaller and the stacking height is higher. The methylene structure will promote the stacking of planar molecules and promote the nucleation of mesophase spheres. The appropriate heat treatment temperature and heat treatment time are conducive to the growth of mesophase spheres and the subsequent fusion, thereby forming a wide-area streamlined mesophase structure. In this link, the methylene structure plays the role of connecting planar molecules. When the temperature is too high or the pressure is too high, the stacked planar molecular structure will decompose.
[0034] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing mesophase asphalt by using polycarbonate modified impregnated asphalt, characterized in that: The following steps are involved:
1. Mixing polycarbonate and impregnated asphalt; 2. The mixture is heated and carbonized.
2. The method for preparing mesophase asphalt by using polycarbonate modified impregnated asphalt according to claim 1, characterized in that: The molecular weight of the polycarbonate is 500-6000.
3. The method for preparing mesophase asphalt by using polycarbonate modified impregnated asphalt according to claim 1 or 2, characterized in that: The softening point of the impregnated asphalt is 80-130° C., the toluene insoluble matter is ≥7%, and the quinoline insoluble matter is ≤0.7%.
4. The method for preparing mesophase asphalt by using polycarbonate modified impregnated asphalt according to claim 3, characterized in that: The softening point of the impregnated asphalt is 80-130° C., the toluene insoluble matter is ≥7%, the quinoline insoluble matter is ≤0.7%, the coking value is ≥45%, the ash content is ≤0.1%, and the volatile matter is ≤60%.
5. The method for preparing mesophase asphalt by using polycarbonate modified impregnated asphalt according to claim 3, characterized in that: The weight ratio of the polycarbonate to the impregnating asphalt is 1:(5-20).
6. The method for preparing mesophase asphalt by using polycarbonate modified impregnated asphalt according to claim 3, characterized in that: The carbonization atmosphere is nitrogen, the carbonization heating rate is 2~6℃ / min, the carbonization temperature is 340~400℃, and the carbonization time is 5~10h.
7. The method for preparing mesophase asphalt by using polycarbonate modified impregnated asphalt according to claim 6, characterized in that: Before carbonization, the polycarbonate and impregnated asphalt mixture were purged with nitrogen for 10-20 min.